May neuroscience be lawyers’ weapon? - Skoczeń, Nikodem; Olajossy, Marcin (Current Problems of Psychiatry, 2015)
For ages, philosophy, ethics and legal sciences have been focusing on explaining issues like morality, free will, responsibility and guilt. This research is increasingly referring to achievements of science and technology in examination of the structures of the nervous system, their activity and roles they play in psychic processes. In order to draw conclusions about penal responsibility based on the scans of criminals’ brains, we need a serious, well-verified knowledge providing information about what kind of brain activity is linked to free will and which poses a threat to it. The results of the examination using the fMRI are incredibly interesting and they have been very fruitful in recent years. Blood-flow visualization techniques showing chosen areas of the brain are now available. The technology of pattern analysis in many volumetric elements (voxels) has been a real breakthrough. It identifies patterns using the data generated by fMRI and this enables the researcher to find a link between psychic phenomena and the observed patterns of brain activity. Authors present chosen situations in which responsibility for the committed act gives rise to a number of doubts with respect to the factors affecting the structure and activity of the brain. Social issues connected with the sense of safety and belief in existing legal order cannot be omitted because the law and judicature are considered to be the rightful fundaments of civilization. Achievements in medical science, psychology and philosophy are increasingly becoming the subject of discussion concerning legal issues, like decisions of courts. Yet, there is a need for some further research which may improve the earnest and objective analysis of these issues. Would neuroscience ever be lawyers’ main argument? If so, when could it be really helpful? It goes without saying that the nearest future will bring answers to these questions.